Genetic Selection Based on a Ste6*C-HA-Ura3 Substrate Identifies New Cytosolic Quality Control Alleles in Saccharomyces cerevisiae. Issue 6 (1st June 2020) - Chan, Shu Ning; Prasad, Rupali; Matsudaira, Paul
Abstract: Protein quality control in the cytosol (CytoQC) is an important cellular pathway consisting of a network of components which monitor the folding of cytosolic proteins and ensure the efficient removal of aberrant ones. Our understanding of CytoQC mechanisms is limited in part by the ability of current approaches to identify new genes in the pathway. In this study, we developed a CytoQC reporter substrate, Ste6 *C-HA-Ura3, for a new genetic selection of spontaneous CytoQC mutations in the yeast Saccharomyces cerevisiae . In addition to UBR1, which encodes for a known CytoQC E3 ligase, we identified six new CytoQC candidates. In the preliminary characterization of two mutants, we found that Doa4 is involved in the degradation of misfolded substrates while Pup2 functions in the selectivity of CytoQC and ERAD substrates. Overall, the strategy demonstrates the potential to identify novel genes and advance our understanding of CytoQC.